2016
DOI: 10.2169/internalmedicine.55.5813
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Kaposi's Sarcoma Complicated by the Immune Reconstitution Inflammatory Syndrome in an HIV-infected Patient

Abstract: We herein report a case of laryngeal Kaposi's sarcoma (KS) complicated by immune reconstitution inflammatory syndrome in a human immunodeficiency virus (HIV)-infected patient. The patient initially presented with KS involving the larynx, which was successfully treated with pegylated liposomal doxorubicin (PLD) and antiretroviral therapy (ART). PLD was discontinued after 2 courses because of a marked clinical improvement; however, the patient experienced progressive odynophagia and dyspnea 2 months after the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The cases presented by us are cases of classical KS, composed of spindle-shaped tumor cells arranged in bundles that intersected and formed numerous slits occupied by blood or lymphatic vessels. Similar to other authors [ 10 , 33 , 34 ], we showed that the tumor cells were positive for anti-CD31, anti-CD34 and anti-D2-40 antibodies, which suggests their vascular origin. The absence of the IHC reaction to the anti-CK AE1/AE3 antibody excludes the epithelial nature of the tumor cells, and the absence of the anti-HMB45 antibody reaction excludes the presence of a melanoma.…”
Section: Discussionsupporting
confidence: 91%
“…The cases presented by us are cases of classical KS, composed of spindle-shaped tumor cells arranged in bundles that intersected and formed numerous slits occupied by blood or lymphatic vessels. Similar to other authors [ 10 , 33 , 34 ], we showed that the tumor cells were positive for anti-CD31, anti-CD34 and anti-D2-40 antibodies, which suggests their vascular origin. The absence of the IHC reaction to the anti-CK AE1/AE3 antibody excludes the epithelial nature of the tumor cells, and the absence of the anti-HMB45 antibody reaction excludes the presence of a melanoma.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 50 articles and 77 patient cases met our inclusion criteria, including 13 articles from our reference list search. There were 15 case series, 1,11,17,18,22‐34 34 case reports, 8,12,14,15,19,35‐63 and 1 prospective case‐control study 1 published between 1965 and 2020, with an aggregate level of evidence 3b per the Oxford Centre for Evidence‐Based Medicine. Individual patient data and demographic information were documented in 45 articles (67 patients) of the 50 identified (77 patients; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Gnepp 17 Case series True vocal folds Gridelli 42 Case report True vocal folds Trunk, upper and lower extremities Karatayli-Ozgursoy 25 Case series Subglottis Kato 43 Case report Epiglottis Face, trunk, extremities, oral cavity Kucuk 44 Case report Epiglottis Lawson 45 Case report Ventricular folds, right false vocal fold Levy 60 Case report Right true vocal fold Widespread cutaneous, rectal mucosa, soft palate, right true vocal fold Liao 46 Case report Epiglottis, aryepiglottic folds Mantilla 26 Case series Subglottis Large mass involving the epiglottis and aryepiglottic folds Marino 11 Case series Right true vocal fold Trachea, lower extremities Thickening hyperdensity of the laryngeal vestibule and the right vocal fold Meyers 62 Case report True vocal folds Hands, postauricular regions, left tonsillar fossa, left lateral pharyngeal wall and pyriform sinus to the level of the arytenoids Miner 47 Case report Epiglottis, left pyriform sinus Soft palate, left faucial tonsil Large pharyngeal mucosal space involving the left faucial tonsil, entire (continued) 28 Case series Epiglottis, arytenoids Hypopharynx, palate, tonsils, thighs, axilla, lower extremities, inguinal and axillary nodes Ribeiro 50 Case report Arytenoids and glottis Trachea Roy 51 Case report Below the epiglottis, true vocal folds Lungs, face, neck, upper trunk, tongue, posterior pharynx, multiple lymph nodes Schiff 18 Case series Epiglottis Left hand Server 52 Case report Epiglottis, aryepiglottic folds Sumarroca 53 Case report Neck, scalp, abdomen, legs, scrotum, tongue, palate Taheri 54 Case report True and false vocal folds 20 3 18-mm polypoid mass seen on left side of glottic space with invasion to the anterior commissure; involvement of the true and false vocal cords Tahir 55 Case report Transglottis Tami 56 Case report Epiglottis, aryepiglottic folds ''Diffuse lesions''…”
Section: Management and Outcomesmentioning
confidence: 99%